A low lasing threshold and widely tunable spaser based on two dark surface plasmons. Issue 1 (December 2017) - Huo, Yanyan; Jia, Tianqing; Ning, Tingyin; Tan, Chaohua; Jiang, Shouzhen; Yang, Cheng; Jiao, Yang; Man, Baoyuan
Abstract We theoretically demonstrate a low threshold and widely tunable spaser based on a plasmonic nanostructure consisting of two sets of disk-rings (TSDR). The TSDR nanostructure supports two dark surface plasmons (SPs), which are excited simultaneously by two bright SPs at Fano dips. The two dark SPs support lower effective mode volume, higher quality factor and higher Purcell factors. When the dark SPs serve as the pumping and lasing mode of a spaser, the spaser has a lower lasing threshold, a higher pump absorption efficiency and a lower threshold absorbed pump power than the spaser based on a bright SP. In addition, the lasing and pumping wavelengths of the spaser proposed in this article can each be tuned over a very wide wavelength range. Our results should be significant for the development of spasers.